Russian Privatization: Catalyst for the Elite - Coulloudon, Virginie (Tufts Archival Research Center, 2005)
Volume 22, Issue 2. Summer/Fall The history of privatization in Russia is riddled with scandals: privatization influenced the creation of the present elite structure and may further transform Russian decision-making in the foreseeable future.